Examining student leadership skills of students in a Chinese University : basis for the student leadership development model - Guognang, Zhao (Manila : National University, 2024)
This study focuses on exploring the skills involved in college students leadership, the ways to improve college students leadership development and the strategies to improve college students leadership development to construct model of student leadership development and provide references for college students leadership development.
Chapter 1. Introduction -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Results and Discussion -- Chapter 5. Summary, Conclusion and Recommendation -- References.
Research Design : Qualitative research
Includes bibliographical references.
Keywords: LEADERSHIP